Literatura jako pole walki. Casus Judasza Iskarioty - Jankowska , Małgorzata (Przestrzenie Teorii, 2024)
The article analyzes some of the representations of Judas Iscariot in modern apocryphal literary works. The aforementioned representations are of subversive character towards the canon and as such they illustrate various inner-cultural tensions and the dynamics of culture. From that point of view literature can be seen as a battlefield in which marginalized discourses clash with the hegemonic, religious one. Areas of tension are diversified: from politics (power, exploitation, social justice), through critique of religion and religious institutions, to “narratives of conflict” between various systems of beliefs or worldviews.